Relationship between Serum Ferritin Levels and Dyslipidemia in Korean Adolescents. - Young-Eun Kim; Do-Hoon Kim; Yong-Kyun Roh; Sang-Yhun Ju; Yeo-Joon Yoon; Ga-Eun Nam; Hyo-Yun Nam; Jun-Seok Choi; Jong-Eun Lee; Jung-Eun Sang; Kyungdo Han; Yong-Gyu Park (PLoS ONE, 2016)
BACKGROUND:Ferritin is associated with various cardiometabolic risk factors such as dyslipidemia, hypertension, obesity, and insulin resistance in adults. We aimed to study the association between serum ferritin levels and dyslipidemia in adolescents, because dyslipidemia is considered an important modifiable cardiovascular risk factor in the young. METHODS:We analyzed 1,879 subjects (1,026 boys and 853 girls) from the 2009-2010 Korean National Health and Nutrition Examination Survey IV. Subjects were categorized into quartiles according to their lipid parameters, which were classified according to age and gender. Those in the highest quartile groups for total cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride concentrations were diagnosed as having dyslipidemia. Those in the lowest quartile for high-density lipoprotein cholesterol (HDL-C) values were diagnosed with abnormal levels. RESULTS:In boys, total cholesterol, LDL-C, and triglyceride concentrations were significantly correlated with serum ferritin levels. In both boys and girls, serum ferritin levels were negatively associated with HDL-C values, even after adjusting for all covariates. Furthermore, there was no significant correlation between serum ferritin levels and total cholesterol, LDL, and triglyceride concentrations in girls. CONCLUSION:Serum ferritin levels were significantly associated with major dyslipidemia parameters, more prominently in boys than in girls, and this association represents a cardiometabolic risk factor.